1997
DOI: 10.1007/bf01240124
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of lysosomal cysteine proteases are decreased in renal cell carcinoma compared with normal kidney

Abstract: Renal cell carcinoma contains significantly lower concentrations of the lysosomal cysteine proteases, cathepsins B, C, H, L and S, than does normal kidney, as shown by several methods, such as activity determination, enzyme-linked immunosorbent assay, immunoblotting and immunohistochemistry. The same low levels of enzyme activity and concentration have been determined in renal cell carcinoma metastases in the lung. Our results on the decreased concentration of cysteine peptidases at the protein level would see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…64 Interestingly, there are some indications that success of therapeutic trials targeting MMP activity is linked to the lack of cathepsin B in the tumors. For example, inhibition of MMP activity in renal cell carcinoma, a type of cancer with exceptionally low levels of cathepsin B, 65 was one of the rare MMPI trials where the overall survival of the patients was significantly prolonged. 66 Our results are consistent with the initial observations that MMPs act mostly as regulators of tumor angiogenesis, 13,14 while cysteine cathepsins contribute to invasion potential of the tumors.…”
Section: Discussionmentioning
confidence: 99%
“…64 Interestingly, there are some indications that success of therapeutic trials targeting MMP activity is linked to the lack of cathepsin B in the tumors. For example, inhibition of MMP activity in renal cell carcinoma, a type of cancer with exceptionally low levels of cathepsin B, 65 was one of the rare MMPI trials where the overall survival of the patients was significantly prolonged. 66 Our results are consistent with the initial observations that MMPs act mostly as regulators of tumor angiogenesis, 13,14 while cysteine cathepsins contribute to invasion potential of the tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Sir, In a recent paper published in this journal, Kirschke et al (1997) reported that renal cell carcinomas contained lower concentrations of cathepsins B, C, H, L and S than normal kidney parenchyma. The author demonstrated decreased levels both by activity measurements and protein determinations, such as enzyme-linked immunoassays and immunoblotting.…”
mentioning
confidence: 99%
“…It has been suggested that the balance between proteases and their endogenous inhibitors, in the case of cathepsins the so-called cysteine protease inhibitors (CPI), determines the invasive and metastatic characteristics of tumour cells (Twining 1994). We therefore read the publication of Kirschke et al (1997) with great interest because our research is engaged in the same ®eld. Since we have carried out experiments measuring both cathepsins and CPI, we will soon report on them to complement the data and conclusions of Kirschke et al (1997).…”
mentioning
confidence: 99%
See 2 more Smart Citations